Potensi Enzim Bromelin Sari Buah Nanas (ananas comosus l.) Dalam Meningkatkan Kadar Protein Pada Tahu - Purwaningsih, Indah (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Tofu is one of processed soybeans that have a high nutritional value and low price. Levels of protein in tofu can be enhanced by enzymatically. One of the protease enzyme which is commonly used in the food industry is bromelain enzyme. The bromelain enzyme in pineapple is widely available. The purpose of this study was to determine the effect of the bromelain enzyme from pineapple juice to protein content by examining the enzyme concentration and incubation time to get the best protein content.This research was quation experiment. The experimental design for this research was randomized block design with 2 factors. Factor I consist of 4 levels (enzyme concentration 35%, 40%, 45% and 50%) and factor II consist of 2 levels (incubation period with enzyme of 6 and 12 hours). The data obtained were then analyzed statistically by multiple linear regression test.The results showed that the best protein content was obtained from the preparation of tofu with the addition of bromelin enzyme from pineapple juice with concentration of 50% and with the incubation time for 12 hours, that is 16,6195%. Statistical test results obtained value of p <0.05, so it can be concluded that there were a relationship/correlation between the enzyme concentration and incubation time to the protein content. Based on the results of research can be suggested that bromelin enzyme from pineapple juice can be used to increase protein content in tofu.